Black Soldier Fly Larval Frass: A Multifaceted Organic Source for Sustainable Agriculture - Reddy, K. Vinay; Mahesh, N.; Imran, G. M.; Reddy, A. Srikar; Susmitha, K.; Bhanuchander, G. (Chronicle of Bioresource Management, 2025)
Black Soldier Fly Larval (BSFL) frass as a sustainable and effective organic fertilizer amid rising concerns over declining soil fertility and limited organic nutrient sources. Derived from insect excreta, chitin and undigested matter, frass is nutrient rich and boosts plant growth, soil health and microbial activity. Its nutrient content is influenced by the larvae’s feed substrate, making it adaptable. Frass improves nitrogen use efficiency, suppresses diseases and enhances crop yield. Beyond its application as fertilizer, it can be used in growing media, soil amendments, animal feed, and biochar production. BSFL frass also contributes to waste recycling, turning organic waste into high-value inputs for agriculture. Its efficacy across various crops and soil types, advocating for its broader adoption in sustainable agriculture and agroecosystem management, particularly in addressing the nutrient deficiencies prevalent in Indian soils.